2002
DOI: 10.1128/cdli.9.3.698-703.2002
|View full text |Cite
|
Sign up to set email alerts
|

Importance of M-Protein C Terminus as Substrate Antigen for Serodetection of Equine Arteritis Virus Infection

Abstract: Equine arteritis virus (EAV),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The BVDV NS3 antiserum used in this study was raised in rabbits against recombinant NS3∆50 (rNS3∆50) fusion proteins expressed in Escherichia coli [16,20] using the pEt-21b expression vector (Novagen, Madison, USA). The cells were washed in phosphate-buffered saline (PBS) solution, pH 7.3, and lysed in standard SDS-PAGE sample buffer.…”
Section: Expression Of Bvdv Ns3 and Ns3∆50 In Mammalian Cells By Westmentioning
confidence: 99%
See 1 more Smart Citation
“…The BVDV NS3 antiserum used in this study was raised in rabbits against recombinant NS3∆50 (rNS3∆50) fusion proteins expressed in Escherichia coli [16,20] using the pEt-21b expression vector (Novagen, Madison, USA). The cells were washed in phosphate-buffered saline (PBS) solution, pH 7.3, and lysed in standard SDS-PAGE sample buffer.…”
Section: Expression Of Bvdv Ns3 and Ns3∆50 In Mammalian Cells By Westmentioning
confidence: 99%
“…Total cell extract proteins were fractionated by 15% SDS-PAGE under reducing conditions and electrotransferred onto nitrocellulose membranes. Western immunoblotting on cell extracts was performed using, as the blocking reagent solution, 5% nonfat dried milk solids and 0.05% Tween 20 in PBS [16]. The blot was incubated with rabbit preimmune serum and BVDV NS3∆50-specific antiserum for 2 h at room temperature.…”
Section: Expression Of Bvdv Ns3 and Ns3∆50 In Mammalian Cells By Westmentioning
confidence: 99%
“…In order to delineate the region in the (+) strand of EAV leader RNA that was involved in interactions with cell proteins, overlapping deletion mutants of the leader RNA (+), strand were generated by inversed PCR [10] from plasmid pEAVL(+) using appropriate primers. These mutants spanned nucleic acids 1-70, 51-115, 96-160, and 140-206 of the EAV leader RNA (+) strand, respectively.…”
mentioning
confidence: 99%
“…These studies indicated that the major N protein epitope that reacts with anti-EAV equine sera is located within the amino acid residue segment from 1 to 69 in the terminal region of the protein. Similarly, it has been demonstrated previously that only the carboxyl-terminal sequence (aa 88 to 162) of the M protein is necessary to identify equine serum antibodies specific to the EAV M protein; it was further suggested that this region should be useful for the serodetection of EAV-infected horses (37). On the basis of the foregoing data, it was decided to express the full-length GP5 , M , and N 1-110 proteins, various antigenic regions of GP5 (aa 1 to 116, 75 to 112, and 55 to 98), and the M 88-162 and N 1-69 proteins as bacterial fusion proteins for use in MIAs to detect antibodies to EAV.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequence 5Ј-CACC-3Ј was added at the 5Ј end of each primer for directional cloning into the pET TOPO vector (Invitrogen, Carlsbad, CA) ( Table 1). The full-length ORFs 5, 6, and 7 (which encode full-length GP5, M, and N proteins, respectively), as well as the coding regions for the amino-terminal ectodomain (amino acids [aa] 1 to 116) and two antigenic regions (aa 55 to 98 and aa 75 to 112) of the GP5 protein (14,15,49), the antigenic carboxyl terminus (aa 88 to 162) of the M protein (37), and the antigenic amino terminus (aa 1 to 69) of the N protein (16), were PCR amplified from the plasmid containing the complete genomic sequence of the EAV virulent Bucyrus strain (pEAVrVBS; GenBank accession number DQ846751) (9) by using Pfu DNA polymerase enzyme (Stratagene, La Jolla, CA) according to the manufacturer's instructions. The individual PCR products were concentrated using a Centricon centrifugal filter unit (Ultracel YM-30; Millipore, Billerica, MA) and purified using a commercial kit (QIAGEN, Valencia, CA).…”
Section: Cellsmentioning
confidence: 99%